The value of the local wisdom of Karma phala in the practice of accountability of the traditional system of the village of Tenganan Pegurinsingan - Dharmawan, Nyoman Ari Surya; Hariadi, Bambang; Adib, Noval (Accounting Department,, 2023)
Objective – This study wants to uncover the value of local wisdom behind the accountability practices implemented by the Balinese Customary Institutions. Design-Method—This type of research is qualitative and uses an ethnomethodological approach. This approach is chosen to explore research problems by understanding the daily life of the subject being studied. Findings—This study found that accountability practices applied to Indigenous institutions are certainly based on phala karma. Karma phala is rooted in two words: karma, which means